RBBP6 Is Abundantly Expressed in Human Cervical Carcinoma and May Be Implicated in Its Malignant Progression. Issue 11 (March 2019) - Dlamini, Zodwa; Ledwaba, Thokozile; Hull, Rodney; Naicker, Sarala; Mbita, Zukile
RBBP6 is a novel gene encoding splicing-associated proteins. There are 3 protein isoforms (isoforms 1-3). RBBP6 isoforms 1 has been shown to interact with both p53 and Rb. It also plays a role in the induction of apoptosis and the regulation of the cell cycle. The expression of RBBP6 has been documented in several cancers but RBBP6 expression in cervical cancer has not been well studied. The aim of this study was to establish expression levels and tissue distribution of the RBBP6 gene products at both protein and messenger RNA (mRNA) levels in cervical cancer by immunocytochemistry and in situ hybridization (ISH). A link between RBBP6 expression, apoptosis, and cervical cancer progression was also investigated. RBBP6 mRNA was expressed in the nuclei and cytoplasm of normal and tumour cervical epithelium. In general, expression was high in the cytoplasm and nuclei of moderately differentiated and invasive carcinoma. Immunolabelling results were confirmed by image analysis and ISH experiments. Apoptosis assays using TUNEL correlated with the expression of the RBBP6 gene in all examined cases. This is the first report on the abundant expression of RBBP6 in cervical cancer and its involvement in the malignant progression of cervical cancer. Because of the high expression and corresponding pro-apoptotic activity observed in cervical cancer cells in this study, we suggest that RBBP6 is involved in the malignant progression of cervical cancer. RBBP6 proteins can therefore be targeted for therapeutic interventions against cervical cancer.